Vacuum enclosures for solar thermal panels Part 1: Fabrication and hot-box testing. (1st November 2018) - Arya, Farid; Moss, Roger; Hyde, Trevor; Shire, Stan; Henshall, Paul; Eames, Philip
Highlights: Vacuum Flat Plate Enclosures were fabricated involving Ultrasonic Soldering techniques. Heat transfer in vacuum space was theoretically studied. Thermal properties of the fabricated enclosures were tested using a hot box calorimeter. Heat flow through the individual components of the vacuum enclosures were theoretically predicted. Infrared thermography was undertaken on the vacuum enclosures with different internal vacuum pressures. Abstract: Non-concentrating solar thermal collectors are generally available in two forms, flat plate or evacuated tube. Recently a third configuration, the evacuated flat plate, has attracted interest due to enhanced performance and aesthetic characteristics. By isolating a solar absorber in a vacuum space (<1 Pa) heat loss from the absorber can be minimized resulting in improved efficiency. In addition the improved thermal insulation performance of evacuated panels over conventional glazing systems makes them attractive solutions for integration into energy efficient building facades. This two part paper describes the design, construction techniques and thermal performance of two vacuum enclosures, fabricated at Ulster University, as prototype components for evacuated flat solar collectors. The first enclosure consists of two glass panes sealed to an edge spacer and separated by an array of support pillars on a regular square grid to form a narrow evacuated space. The second enclosure incorporates an uncooled copper sheet to represent a solar thermal absorber. The enclosures were tested at three conditions i.e. with an internal pressure of high vacuum (0.0021 Pa), low vacuum (8.4 Pa) and no vacuum (atmospheric pressure). Part 1 of this paper describes the fabrication process for the vacuum enclosures and the measurement of their thermal insulation properties using a hot box calorimeter. The theory of heat transfer through an enclosure with support pillars is discussed; experimental results are compared with mathematical models predictions. A fabrication methodology has been successfully established and a U-value of 1.35 W/m 2 K for an enclosure with an internal pressure of 0.0021 Pa has been demonstrated. The experimental results are in good agreement with the predictions. Part 2 of this paper describes solar simulator testing of the enclosure containing a copper plate. The highest stagnation temperature (121.8 °C) was reached under steady-state conditions in the high vacuum test and was in good agreement with predictions. The transient plate and glass surface temperatures were measured and found to be consistent with the predicted curves.